Feasibility of a hearing screening programme using DPOAEs in 3-year-old children in South Auckland. (February 2021) - Su, Emily; Leung, Joan H.; Morton, Randall P.; Dickinson, Louise J.; Vandal, Alain C.; Balisa, Nelson B.; Purdy, Suzanne C.
Abstract: Objectives: In New Zealand (NZ), permanent hearing loss is associated with higher levels of socioeconomic deprivation, and is more prevalent amongst Māori and Pacific than NZ European children. Many of these hearing losses are detected through newborn hearing screening, however there is a need to screen children again later, to look for childhood hearing losses that are either late-onset, progressive, or acquired. This study evaluated the feasibility of implementing an objective screening protocol that includes otoscopy, distortion product otoacoustic emission screening (DPOAEs), and tympanometry. It also evaluated the feasibility of using Early Learning Centres (ELCs) to contact families, recruit, and test 3-year-old children from an area of high socioeconomic deprivation in Auckland, New Zealand. Methods: Sixty-one 3-year-old children were recruited from ELCs within the Counties Manukau District Health Board (CMDHB) region which services the geographical area of South Auckland. The first part of the screening protocol consisted of otoscopy, DPOAEs, and tympanometry. Children identified with hearing loss and/or middle ear problems were either referred directly to Otolaryngology/Audiology at the local hospital or invited back for a re-screen 4–8 weeks later. Children who were referred from the screening were followed up to track and document their subsequent clinical pathway through the public health system. Results: Mean overall time for the screening protocol was 4.1 minutes. The combination of otoscopy, DPOAEs, and tympanometry was well accepted by the 3-year-old children. DPOAE amplitude and signal-to-noise ratio results significantly differentiated between different tympanometry results, providing support for this combination of measures to accurately screen for hearing loss and/or middle ear disease. Thirty-eight of the 61 children (62%) passed the screening protocol. Of the remaining 23 children, five were referred to the hospital after not passing the screening, but following more in-depth audiological testing, were discharged with normal hearing. Six children referred to the hospital were diagnosed with varying degrees of conductive hearing loss, and two of the six received grommet insertion surgery. The remaining 12 children who were referred to the hospital were lost to follow-up, highlighting challenges for the families to successfully navigate the current public health system. Conclusion: This study demonstrates that identifying hearing loss and ear disease in 3-year-old children in the pre-school setting is feasible. A number of barriers were identified in the current health system that contribute to a large proportion of children referred with suspected hearing loss and ear disease being unsuccessful in accessing Otolaryngology/Audiology clinical care through the local hospital.